Authorship and Control over Thoughts. (November 2014) - Vosgerau, Gottfried; Voss, Martin
Abstract The 'mineness' of thoughts has often been accepted as indubitable in philosophy. However, the symptom of thought insertion in schizophrenia seems to be an empirical counterexample to the dictum that every introspected thought is one's own. We present a thorough conceptual analysis of mineness of thought, distinguishing between ownership and authorship (thought agency). We argue that it is indeed a conceptual truth that introspected thoughts are owned by the introspector. However, there are everyday and pathological cases of thoughts, for which we do not ascribe authorship to ourselves. To explain inserted thoughts, however, we need an additional factor which is constituted by the lack of control over inserted thoughts (as with intrusive thoughts in patients suffering from OCD). We present a review of empirical data on thought control and thought insertion in the light of the conceptual analysis. We conclude with a summary of the most important future direction of research.